International Political Economy: Some African Applications. - Collier, P (OUP, 2008)
Modern theories of political economy analyze the sources of political power and their uses for economic ends. The key instruments are taxation and regulation. Although international political economy treats states as its unit of analysis, the number of states is endogenous. This is highly pertinent for Africa, which has far more states relative to its population than other regions. Africa's many small states face acute difficulties of supplying the core public good of enforced justice and I apply the new economics of lawlessness developed by Dixit to show the consequences. I argue that due to the difficulties of supplying this key public good from within the state, Africa needs to have more recourse to the international provision: both through inter-state cooperation within the region, and through global provision.